BALANCED LABOUR INTENSITY AS AN ESSENTIAL CONDITION FOR EDUCATION QUALITY ASSURANCE - Nikolay V. Filonov; Nikolay N. Malivanov (Высшее образование в России)
The article analyzes education quality in terms of distribution of labour intensity of disciplines and amount of educational material of an academic program. The authors offer a special method to determine labour intensity and the amount of educational material based on evaluation reading speed and learning rate of educational material. The number of pages of recommended literature on educational issues of syllabus is used as a unit of measurement of the amount of educational material. This approach results from the fact that over 67% of students use paper copies not electronic resources while studying. Learning rate of a discipline is calculated by means of a specially developed technique. Reading speed is determined experimentally basing on understanding rate of content of texts in Humanities and technical texts. The statistical sample included only the results with the correct answers on the text content. When the amount of labour intensity in academic hours, the rate of material learning and the speed of meaningful reading are given, it is possible to determine the amount of educational material in pages of the main textbook from a discipline curriculum of the academic program. The described approaches used to determine the amount of labour intensity and the amount of educational material of disciplines have particular importance for reaching equivalence and harmonization of curricula in terms of networking technologies and when training specialists according to double degree scheme.